Variasi Debit Dan Temperatur Udara Pengering Flash Dryer Terhadap Hasil Pengeringan - Rudyantoro, Pondra, Ir. Sartono Putro, MT, Dr. Marwan Effendy (2016)
Preheating of air in the dryer has an important role in drying process. This experiment discusses the influence of air flow and their temperature on the drying quality of tapioca. This research begins with the assembly of the components of "flash dryer". The intake of air blower is varied at 0.094, 0.085 and 0.075 m3/s, while the air temperature on the water heater is conditioned by 95, 105 and 115 °C. Blower is installed on the "air heater" to supply hot air for drying and also to pust dry powder under the cyclone. In order to collect data of air temperatur, a thermocouple is placed on the mounted pipe of hammer mill and a thermometer is installed the mounted pipe of air heater. The result show that the lowest density of flour is 0.517 kg/l with the discharge air is 0.075 m3/s and temperature 115 °C. While the highest density of flour is 0.555 kg/l with the discharge air is 0.094 m3/s and temperature 95 °C.